Introduction to food toxicology - Shibamoto, Takayuki; Bjeldanes, Leonard F. (Food science and technology international series, 2009)
The rapidly expanding field of food safety includes many developments in the understanding of the entire range of toxic compounds found in foods. This title explores these developments, providing a core understanding of the basic principles of food toxicology